How many meals and snacks do Brazilians eat a day? Findings from the 2017-2018 Brazilian National Dietary Survey - Paulo Rogério Melo Rodrigues; Luana Silva Monteiro; Thaís Meirelles de Vasconcelos; Luiz Eduardo da Silva Gomes; Iuna Arruda Alves; Valéria Troncoso Baltar; Bartira Mendes Gorgulho; Edna Massae Yokoo; Rosely Sichieri; Rosangela Alves Pereira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
The habit of eating specific meals has been addressed in several studies, but the evaluation of meal patterns has received less attention. This study aimed to describe the meal patterns of the Brazilian population. A complex sampling design was used to select the 46,164 ≥ 10-year-old individuals examined in the Brazilian National Dietary Survey. Food consumption was assessed by two non-consecutive 24-hour recalls applied throughout a one-week period. The exploratory data analysis approach was used to determine the meal patterns, i.e., how individuals combined the main meals (breakfast, lunch, dinner) and snacks (morning, afternoon, evening/night) throughout the day. The most common meal patterns were three main meals + one snack, reported by 25.1% of the individuals, and three main meals + two snacks (24.6%). Other meal patterns identified were: three main meals + three snacks (18.5%); three main meals and no snacks (10.9%); one or two main meals + two snacks (7.4%); one or two main meals + one snack (6.9%); one or two main meals + three snacks (4.2%); and one or two main meals and no snacks (2.3%). Meal patterns varied according to gender and age group, and on typical versus atypical food consumption days. We found that eight patterns characterized the daily meal consumption in Brazil. Furthermore, around 80% of the population had three main meals every day and about 13% did not report having any snacks. The characterization of meal habits is important for tailoring and targeting health promotion actions.